2023
DOI: 10.3390/microbiolres14030086
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Epidemiology of Clostridioides difficile Infection in Central India: A Prospective Observational Cohort Study

Rima Biswas,
Nick Pinkham,
Seth T. Walk
et al.

Abstract: This prospective observational cohort study aimed to establish and compare baseline rates of Clostridioides difficile infection (CDI) in community and hospitalized patients in Nagpur and rural Melghat Maharashtra, including adults aged ≥18 years with a diagnosis of diarrhoea as defined as 3 or more loose stools in a 24 h period. All diarrhoeal samples were tested for CDI using the C. diff Quik Chek Complete enzyme immunoassay. C. difficile-positive stool samples were characterised by toxigenic culture, antimic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(59 reference statements)
0
0
0
Order By: Relevance
“…Various studies conducted across India have revealed that there is a wide variation in the CDI prevalence ranging from 1.2 to 22% as shown in Table 2 . 16 – 23 In contrast, studies from developed nations such as the UK, the USA, and Germany have reported a lower prevalence ranging from 7.4 to 12.7%. 24 26 In this study, the CDI prevalence in a 6-year-long period was reported to be 7.6%, which is identical to the studies conducted across India by Monaghan et al and Sachu et al where they reported a prevalence of 6.5% and 8.8% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies conducted across India have revealed that there is a wide variation in the CDI prevalence ranging from 1.2 to 22% as shown in Table 2 . 16 – 23 In contrast, studies from developed nations such as the UK, the USA, and Germany have reported a lower prevalence ranging from 7.4 to 12.7%. 24 26 In this study, the CDI prevalence in a 6-year-long period was reported to be 7.6%, which is identical to the studies conducted across India by Monaghan et al and Sachu et al where they reported a prevalence of 6.5% and 8.8% respectively.…”
Section: Discussionmentioning
confidence: 99%